LITERATURE REVIEW : EFEKTIFITAS PELVIC ROCKING EXERCISE MENGGUNAKAN BIRTHING BALL TERHADAP KEMAJUAN PERSALINAN PADA IBU PRIMIPARA - Lea Ingne Reffita; Senditya Indah Mayasari; Ummi Halfida; Wili Sinarti; Yaumil Fitriyah; Zidni Karimatun Nisa (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Indonesia's Health Profile in 2019 in general, there was a decrease in maternal mortality during the period 1991-2015 from 390 to 305 per 100,000 live births, if it is associated with the 2015 Millennium Development Goals (MDGs), namely reducing the maternal mortality rate (MMR) to 102/100,000 live births. the maternal mortality rate did not reach the MDGs target. Physiological efforts are made to prevent prolonged labor, such as pelvic rocking exercise using the birthing ball technique. This is also a method that really helps respond to pain in an active way and reduces the length of the first stage of labor in the active phase. This study aims to determine the effectiveness of the implementation of pelvic rocking with a birthing ball on the progress of labor in primiparous women in 2020. This study uses Systematic Literature Reviews (SLR), which is a synthesis of systematic, clear, comprehensive literature studies, by identifying, analyzing , evaluating through the collection of existing data with an explicit search method and involving a critical review process in the selection of studies. In 6 journals, all journals perform pelvic rocking exercise techniques using the birthing ball technique when the mother enters the first stage of the active phase. The conclusion in this study is that all journals reviewed by researchers can be ascertained that all of these journals get the same results, namely stating that using the Pelvic Rocking Exercise technique with the help of a birthing ball can make delivery times for mothers go faster